2022
DOI: 10.1038/s41375-022-01577-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of RUNX3 inhibits normal human myeloid development

Abstract: RUNX3 is a transcription factor dysregulated in acute myeloid leukemia (AML). However, its role in normal myeloid development and leukemia is poorly understood. Here we investigate RUNX3 expression in both settings and the impact of its dysregulation on myelopoiesis. We found that RUNX3 mRNA expression was stable during hematopoiesis but decreased with granulocytic differentiation. In AML, RUNX3 mRNA was overexpressed in many disease subtypes, but downregulated in AML with core binding factor abnormalities, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…RUNX2 is upregulated in multiple cancers and is also found to contribute to glial tumor malignancy 60 . Elevated RUNX3 expression has also been observed in various metastatic cancers, such as leukemia 61 , but in glioma it has been shown to be a tumor suppressor 52 , and in our results, these pathways are enriched in good prognosis. Growing evidence indeed indicates that the roles of RUNX genes in carcinogenesis are cell type-specific and context-dependent.…”
Section: Discussionsupporting
confidence: 70%
“…RUNX2 is upregulated in multiple cancers and is also found to contribute to glial tumor malignancy 60 . Elevated RUNX3 expression has also been observed in various metastatic cancers, such as leukemia 61 , but in glioma it has been shown to be a tumor suppressor 52 , and in our results, these pathways are enriched in good prognosis. Growing evidence indeed indicates that the roles of RUNX genes in carcinogenesis are cell type-specific and context-dependent.…”
Section: Discussionsupporting
confidence: 70%
“…RUNX2 is upregulated in multiple cancers and is also found to contribute to glial tumor malignancy [52]. Elevated RUNX3 expression has also been observed in various metastatic cancers, such as leukemia [53], but in glioma it has been shown to be a tumor suppressor [45], and in our results these pathways are enriched in good prognosis. Growing evidence indeed indicates that the roles of RUNX genes in carcinogenesis are cell type-specific and context-dependent.…”
Section: Discussionsupporting
confidence: 70%
“…In the case of a switch from RUNX1 to RUNX2, it would promote commitment to the pDC lineage because RUNX2 is a key player in differentiation into pDCs [ 42 , 118 ]. Expression levels of the RUNX family would represent an interesting pathway to study in AML, as recently shown with RUNX3, found downregulated in AML with RUNX1::RUNX1T1 transcript and upregulated in AML with normal karyotype [ 119 ]. Of note, high levels of RUNX3 would be associated with poor outcome [ 119 , 120 ].…”
Section: Genetics Of Pdc Proliferation Associated With a Myeloid Diso...mentioning
confidence: 99%
“…Expression levels of the RUNX family would represent an interesting pathway to study in AML, as recently shown with RUNX3, found downregulated in AML with RUNX1::RUNX1T1 transcript and upregulated in AML with normal karyotype [ 119 ]. Of note, high levels of RUNX3 would be associated with poor outcome [ 119 , 120 ].…”
Section: Genetics Of Pdc Proliferation Associated With a Myeloid Diso...mentioning
confidence: 99%